PEDAGOGICAL CHARACTERISTICS OF EDUCATION OF ENVIRONMENTAL LITERACY OF SCHOOL STUDENTS (ResearchJet Journal of Analysis and Inventions, 2022)
This article is devoted to the psychological and pedagogical problems that arise in the improvement of environmental literacy among schoolchildren, and their solutions.